Human antibodies targeting ENPP1 as candidate therapeutics for cancers - Chu, Xiaojie; Baek, Du-San; Li, Wei; Shyp, Taras; Mooney, Brian; Hines, Margaret G.; Morin, Gregg B.; Sorensen, Poul H.; Dimitrov, Dimiter S. (Frontiers in Immunology, 2023)
Ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) is a type II transmembrane glycoprotein expressed in many tissues. High expression levels of ENPP1 have been observed in many cancer types such as lung cancer, ovarian cancer, and breast cancer. Such overexpression has been associated with poor prognosis in these diseases. Hence, ENPP1 is a potential target for immunotherapy across multiple cancers. Here, we isolated and characterized two high-affinity and specific anti-ENPP1 Fab antibody candidates, 17 and 3G12, from large phage-displayed human Fab libraries. After conversion to IgG1, the binding of both antibodies increased significantly due to avidity effects. Based on these antibodies, we generated antibody-drug conjugates (ADCs), IgG-based bispecific T-cell engagers (IbTEs), and CAR T-cells which all exhibited potent killing of ENPP1-expressing cells. Thus, these various antibody-derived modalities are promising therapeutic candidates for cancers expressing human ENPP1.